Detection of Blackhole Attack Using RMBOPB Based Agent - Hassan, Khondekar Lutful; Mandal, JK; Zia, Md Saquib; Shaw, Deepshikha (International Journal of Computer Sciences and Engineering, 2025)
In this paper a novel technique has been introduce to detect black hole attack using Recursive Modulo 2 and Bitwise Operations of Paired Bits (RMBOPB) agent, where RMBOPB agent is fired from a monitoring nodes. The RMBOPB agent traverses throughout the network. If the RMBOPB agent reached to any Blackhole node then it will send the message to the monitor node for the malicious status signal to the monitor node. To implement Blackhole attack in Adhoc On Demane Distance Vector (AODV) routing protocol is taken as MANET routing protocol, and Network Simulator 2 (NS 2.34) is taken as simulation tool. Simulations are done through various node densities and various scenarios. Number of packet receive, packet delivery ratio and throughput is taken as the metric for the compassion of performance of the network. After comparing the every simulation it is seen that the proposed method detect the black hole attack in the network and increase the performance of the network.